Formation of nanostructured and amorphous β-Al3Mg2 based alloys by rapid solidification and mechanical milling - Mukherjee D.; Ande V.; Manna R.; Murty B.S.; Mukhopadhyay N.K. (My University, 2025)
Al-Mg alloys close to β-Al3Mg2 intermetallic phase were processed by melt-spinning and mechanical milling in order to make it nanocrystalline or amorphous alloy. X-ray diffraction, differential thermal analysis and transmission electron microscopy were carried out to investigate the sequential microstructural evolution and stability during the synthesis process. It was found that in the melt-spun ribbons of all the alloys there was no new phase formation but nanophase was observed with a minimum crystallite size of ∼45nm. However mechanically milled alloys yielded nanocrystalline phase with lower crystallite size and amorphous phase in some alloys. The minimum crystallite size was found to be in the range of 8-22nm after 20h of milling. Thermodynamic modeling using the Miedema semi-empirical approach was also done to predict the glass-forming range of the Al-Mg system. From Miedema model it can be inferred that, for the amorphous phase to be more stable than the crystalline solid solution the crystallite size should be below ∼20nm in the present alloy systems. © 2010 Elsevier B.V.